FRESH MINAS CHEESE AGROINDUSTRY - da Silva, Anildo Fernando Rodrigues; Ferrarezi Junior, Edemar; Carrasqueira, Arthur; Caracini, Luiz Gustavo (Revista Interface Tecnológica, 2023)
Cheese is among the products that have great market acceptance, thus bringing a great economic opportunity to our country. The present work has as main objective to show guidelines for the creation of a cheese factory with the main activity of producing Fresh Minas Cheese, and to present results regarding the per capita consumption of cheese, proving to be an economically viable activity. For this study, tools were used such as market analysis and sizing, which makes it possible to verify the conditions of the milk and cheese market, production, exports and imports and the trend of this product in the current market. Also presented will be presented the processes and operations, the equipment used for the production of cheese, the norms and legislations, sizing, structure, and important data about the cheese market in the Brazilian territory and finally the results, which will demonstrate per capita values of Consumption of Fresh Minas Cheese.
Keywords: Viability; Economy; Production; Dairy